PENEGAKAN HUKUM JABATAN NOTARIS DALAM PEMBUATAN PERJANJIAN BERDASARKAN PANCASILA DALAM RANGKA KEPASTIAN HUKUM - Endang Purwaningsih (Lembaga Penelitian Universitas YARSI, 2019)
Notaries, when exercising their authority as public officials, should equip themselves withPancasila values so that they can perform impartially and help contribute to public orderand legal certainty. This research reviews notaries’ implementation of Pancasila values ina bid to achieve legal certainty to any related parties, particularly those involved in legalagreements. This research is normative in nature, featuring legal documents as materialsor literature to analyze and from which conclusions are drawn. The findings of thisresearch suggest that—to have quality notary professionals—the law enforcement fornotary office based on Pancasila values should be done through such measures as: (1)properly and consequently exercising their authorities as notaries as stipulated in UUJNand (2) performing based on Pancasila values, upholding professional ethics with moralintegrity in a way that they value honesty, are aware of their boundaries, and possess thetrue sense of justice. This means that they are not tempted by bribe; they also work notmerely to gather formal evidence without putting the sense of justice into consideration.Thus, the expected qualities of notaries are: (1) having good will, (2) impartial, (3)upholding justice for the sake of legal certainty, (4) respecting shared consensus, (5)upholding agreement on the legal basis, (6) providing the best service on the accountablebasis, (7) upholding professionalism based on codes of ethics, (8) upholding andimplementing Pancasila values, (9) maintaining public trust, (10) exercising authoritieswithin boundaries as stipulated in UUJN (formal authorities), and (11) always upgradingtheir competence, skills, and professional network.